Physical properties of the mature-green golden apple (Spondias Cytherea Sonnerat) / Mohd Haris Ridzuan Ooi Abdullah and Ch'ng Pei Eng - Ooi Abdullah, Mohd Haris Ridzuan; Ch'ng, Pei Eng (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Some physical properties of golden apple (Spondias cytherea Sonnerat) at green-mature stage were determined in this work. The mean wet basis moisture content of the fruit was 89.38 ± 0.48 %. The fruit has an average length, width and thickness of 46.92 ± 2.77 mm, 31.81 ± 1.90 mm and 31.88 ± 1.98 mm, respectively. In terms of its geometric mean diameter, sphericity, aspect ratio and surface area, the reported average values were 36.22 ± 1.84 mm, 77.29 ± 3.30 %, 67.93 ± 4.40 % and 4132.06 ± 417.48 mm2 , respectively. The mean value for mass, volume, true density, bulk density and porosity of the fruit were 26.868 ± 3.963 g, 26100.00 ± 3871.55 mm3 , 1055.14 ± 12.19 kgm-3 , 646.28 ± 58.02 kgm-3 and 38.75 ± 5.46 %, respectively. The average value of static friction coefficient for the fruit against four types of structural surface were found to be ranging from 0.419 ± 0.049 for galvanized steel sheet to 0.475 ± 0.041 for rubber surface. The data obtained in this study may be useful to facilitate the design of machines and tools for postharvest handling and processing of the fruit.